ANALISIS PROFITABILITAS WIRAUSAHA PENJUALAN BENIH IKAN LELE (Clarias Sp) DI BATURAJA TIMUR KABUPATEN OGAN KOMERING ULU (JASEP, 2021)
Entrepreneur Profitability Analysis Sale of Catfish Seeds (Clarias sp) in East Baturaja Ogan KomeringUlu District. The purpose of this study is To analyze the entrepreneurial profitability of catfish seed sellers in East Baturaja Ogan Komering Ulu Regency. Litian Pen this carried out in Baturaja East OKU. Determination location do in a manner on purpose (Purposive) with consideration entrepreneurship sales seed fish catfish ( Clarias sp ) cultivated in Baturaja East districts Ogan Comering Ulu . Method The research in research this is survey method used for obtain fact field with use questionnaire as tool data collector from sales seed fish catfish in King stone East districts Ogan Comering Ulu . Method withdrawal example in the use is sample saturated based on research this because total population small then author take 100% amount population. With thus use all over population without should interesting sample research as an observation unit called as technique census . Where 10 entrepreneurs catfish seed sales were homogeneous with above average area of 2 x 3 m ² and 3 x 6 m². The results showed that analysis and the results research that has been done, then could taken conclusion that is profitability entrepreneurship seed sales fish catfish as much as 6.5 0% then entrepreneurship seed fish catfish in Baturaja East RegencyO , bro Comering Ulu very much t profitable . Keyword : Entrepreneur, Analysis, Catfish Seeds